Adverse cardiovascular events in patients with coronary microvascular dysfunction: results of a 12-month follow-up with a control group - K. V. Kopyeva; A. N. Maltseva; A. V. Mochula; E. V. Grakova; K. V. Zavadovsky (Российский кардиологический журнал, 2023)
Aim. To assess the development of adverse cardiovascular events in patients with non-obstructive coronary artery disease (CAD) and coronary microvascular dysfunction (CMD), identified by dynamic myocardial single-photon emission computed tomography (SPECT), during 12-month follow-up compared with patients without CMD.Material and methods. The study included 118 patients (70 men, mean age, 62,0 [58,0; 69,0] years) with preserved ejection fraction (62 [59; 64] %) and non-obstructive CAD. Serum levels of the N-terminal pro-brain natriuretic peptide were assessed at baseline by enzyme immunoassay. Coronary flow reserve (CFR) was assessed by dynamic SPECT. CFR ≤2 was a CMD marker.Results. Six patients discontinued participation in the study due to loss of contact with them, while the rest were divided into groups depending on CMD presence: group 1 included patients with CMD (CFR ≤2; n=42), and group 2 was the control group and included patients without CMD (CFR >2; n=70). Within 12-month follow-up, 25 patients reported adverse events. According to Kaplan-Meier analysis, the prevalence of adverse cardiovascular events was higher in patients with CMD (45,2%, n=19) than in patients without it (8,6%, n=6) (p<0,001). Multivariate regression analysis showed that the presence of CMD (odds ratio (OR), 2,42; 95% confidence interval (CI), 1,26-5,85; p<0,001) and diastolic dysfunction (OR, 3,27; 95% CI, 2,26-5,64; p<0,001) were independent predictors of poor outcomes. The combination of CMD with diastolic dysfunction more than 5 times increased the risk of adverse events (OR, 5,18; 95% CI, 3,61-11,84; p<0,001).Conclusion. We found that in patients with non-obstructive CAD, the presence of CMD, identified by dynamic myocardial SPECT, was associated with a higher risk of adverse cardiovascular events within 12-month follow-up period than in patients without CMD. At the same time, the combination of CMD with diastolic dysfunction more than 5 times increased the risk of adverse outcomes.